An appraisal of labour productivity in sandcrete block making factories in Minna, Nigeria - Haruna, Nurudeen (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2018)
Sandcrete block are composite building material produced of sand, cement and water, moulded in different sizes. The recognition and widespread of sandcrete blocks and their general application as walling material in Nigeria and other developing countries cannot be overemphasized. Hence, caused serious demand for it, and oblige its high production. As a result, production industries are expected to put more concern on the improvement of efficiency and effectiveness of labour productivity in the production process due to the increasing demand of the materials. Productivity enhancement in any production industries is powered by the level of increase in labour productivity. The aim of any production company is to realize a higher productivity as it was explained to be cost savings and eventually into manager's additional benefits. This study aimed at exploring the process of producing sandcrete block and its labour productivity, identifying and ranking the key management and site related factors on factories in Minna, Nigeria. The data was collected from 84 factories registered under standard organization Nigeria (SON), using structured questionnaire. Findings in this study, shows different stages and standards used for the sandcrete block production. It was found that market, management strategies, delay in materials delivery, equipment breakdown, weather and absenteeism/turnover are the main factors affecting labour productivity in sandcrete block making factories in Minna. In addition, some varieties of techniques were identify to mitigate or minimize the effect of the above mentioned factors. Findings from this study is expected to assist the managers on how to efficiently improve labour productivity in other to meet up the growing demand of sandcrete block in the market and will also serve as a reference material in the future regarding how to enhance labour productivity, contributing to the existing body of knowledge. Keywords: Sandcrete block, Labour Productivity, Management related, Site related, Techniques.